COVID-19-The Potential Beneficial Therapeutic Effects of Spironolactone during SARS-CoV-2 Infection - Katarzyna Kotfis; Kacper Lechowicz; Sylwester Drożdżal; Paulina Niedźwiedzka-Rystwej; Tomasz K. Wojdacz; Ewelina Grywalska; Jowita Biernawska; Magda Wiśniewska; Miłosz Parczewski (MDPI AG, 2021)
In March 2020, coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 was declared a global pandemic by the World Health Organization (WHO). The clinical course of the disease is unpredictable but may lead to severe acute respiratory infection (SARI) and pneumonia leading to acute respiratory distress syndrome (ARDS). It has been shown that pulmonary fibrosis may be one of the major long-term complications of COVID-19. In animal models, the use of spironolactone was proven to be an important drug in the prevention of pulmonary fibrosis. Through its dual action as a mineralocorticoid receptor (MR) antagonist and an androgenic inhibitor, spironolactone can provide significant benefits concerning COVID-19 infection. The primary effect of spironolactone in reducing pulmonary edema may also be beneficial in COVID-19 ARDS. Spironolactone is a well-known, widely used and safe anti-hypertensive and antiandrogenic medication. It has potassium-sparing diuretic action by antagonizing mineralocorticoid receptors (MRs). Spironolactone and potassium canrenoate, exerting combined pleiotropic action, may provide a therapeutic benefit to patients with COVID-19 pneumonia through antiandrogen, MR blocking, antifibrotic and anti-hyperinflammatory action. It has been proposed that spironolactone may prevent acute lung injury in COVID-19 infection due to its pleiotropic effects with favorable renin-angiotensin-aldosterone system (RAAS) and ACE2 expression, reduction in transmembrane serine protease 2 (TMPRSS2) activity and antiandrogenic action, and therefore it may prove to act as additional protection for patients at highest risk of severe pneumonia. Future prospective clinical trials are warranted to evaluate its therapeutic potential.